Local wisdom-based learning of the Maataa tradition: How does it impact students' cultural literacy? - Mursalim, Mursalim; Maftuh, Bunyamin; Supriatna, Mamat (Journal of Innovation and Research in Primary Education, 2025)
Purpose: This study aims to analyze the effect of learning based on the local wisdom of the Maataa tradition on improving the cultural literacy of elementary school students. Method: The research approach used is quantitative with a quasi-experimental design in the form of a pretest-posttest control group design without randomization. The research subjects consisted of 61 fifth-grade students at SDN 63 Buton, divided into two groups: experimental (n = 31) and control (n = 30). The experimental group received learning based on Maataa traditions, while the control group received conventional learning. The intervention was conducted over three weeks with two learning sessions per week. The research measurement tool was a cultural literacy essay test that had undergone expert validation and reliability testing (Cronbach's Alpha = 0.622). Data analysis was performed using an independent samples t-test and N-gain test. Results: The study results showed a significant increase in average scores from pre-test to post-test in the experimental group (from 70.8 to 92.9) compared to the control group (from 70 to 88.7). The t-test yielded a significance value of 0.000 (p < 0.05), indicating a statistically significant difference between the two groups. Additionally, the N-gain score of the experimental group was 0.76 (high category), while the N-gain score of the control group was 0.62 (moderate category). These findings indicate that learning based on the local wisdom of the Maataa tradition effectively enhances students' cultural literacy. Implications: These results emphasize the importance of integrating local cultural values into the learning process as a contextual pedagogical strategy that supports the strengthening of cultural identity and student engagement in social studies learning at the elementary school level.